Novel insights into antimicrobial-resistant, virulent and biofilm-forming Salmonella: Molecular and phenotypic evidence from duck at the human-animal-environment interface - Paul, Aditya; Joardar, Siddhartha Narayan; Samanta, Indranil; Batabyal, Kunal; Dey, Samir; Ghosh, Prakash; Wahed, Ahmed Abd El; Bardhan, Rajarshi; Dhara, Keshab Chandra; Datta, Sanjoy (Frontiers in Microbiology, 2026)
The present study provides first time the comprehensive molecular and phenotypic characterization of antimicrobial-resistant, biofilm-forming, and virulent Salmonella spp. isolated from apparently healthy ducks and their environments in West Bengal, India. A total of 462 samples from Indigenous, Khaki Campbell, and Pekin ducks yielded 436 isolates, of which 42.2% were ESBL producers carrying blaTEM (36.5%), blaCTX−M(20.6%), blaSHV (17.7%), and blaAmpC (32.6%). Sequence analysis revealed multiple clinically relevant alleles, including blaTEM-164, blaCTX−M-15, and blaSHV-45, underscoring their potential public health significance. The isolates were also screened for biofilm genes (csgA, sdiA, rpoS, rcsA), and the virulence gene invA. Biofilm-associated genes were widely distributed (csgA: 54.59%, sdiA: 52.52%, rpoS: 80.28%, rcsA: 63.76%), while 141 (32.34%) of isolates possessed the invA virulence marker. Of 26 selected strains, high multi-drug resistance was detected, mainly against tetracycline and cefixime. Phylogenetic analysis of ESBL gene sequences showed clustering across avian, animal, and clinical (human) Salmonella isolates, indicating potential interspecies transmission and evolutionary divergence. Notably, strong positive correlations were observed among biofilm formation, multidrug resistance, and virulence (τ = 0.656, ρ = 0.765, p < 0.001). Western blotting further identified two unique polypeptide markers (69 and 35 kDa) with diagnostic potential for detecting resistant, virulent, and biofilm-forming Salmonella. In short, these findings highlight, for the first time, duck as silent reservoirs of high-risk Salmonella strains, and propose novel protein markers to facilitate early detection at the human-animal-environment interface.